Carbon Capture by Fossil Fuel Power Plants: An Economic Analysis - İşlegen, Özge and Reichelstein, Stefan (Management Science, 2011)
For fossil fuel power plants to be built in the future, carbon capture and storage (CCS) technologies offer the potential for significant reductions in carbon dioxide (CO 2 ) emissions. We examine the break-even value for CCS adoptions, that is, the critical value in the charge for CO 2 emissions that would justify investment in CCS capabilities. Our analysis takes explicitly into account that the supply of electricity at the wholesale level (generation) is organized competitively in some U.S. jurisdictions, whereas in others a regulated utility provides integrated generation and distribution services. For either market structure, we find that emissions charges near $30 per tonne of CO 2 would be the break-even value for adopting CCS capabilities at new coal-fired power plants. The corresponding break-even values for natural gas plants are substantially higher, near $60 per tonne. Our break-even estimates serve as a basis for projecting the change in electricity prices once carbon emissions become costly. CCS capabilities effectively put an upper bound on the increase in electricity prices resulting from carbon regulations, and we estimate this bound to be near 30% at the retail level for both coal and natural gas plants. In contrast to the competitive power supply scenario, however, these price increases materialize only gradually for a regulated utility. The delay in price adjustments reflects that for regulated firms the basis for setting product prices is historical cost, rather than current cost. This paper was accepted by Gérard P. Cachon, accounting.